Determinants of Green Finance and Good Corporate Governance on Company Value and Profitability in the Banking Industry Listed on the Indonesia Stock Exchange - sinta munilah; Euis Ajizah; D. Muhamad Yamin (JURNAL ECONOMINA, 2026)
As the transition towards a sustainable economy continues, this study examines the influence of green finance and good corporate governance (GCG) on Indonesian banking valuation (PBV), with profitability (ROA) as a mediating variable. Based on panel data from 15 commercial banks listed on the Indonesia Stock Exchange (IDX) (2021–2025) and a random effects model (EViews) analysis, the results show that green finance, good corporate governance, and profitability have no significant effect on the valuation of Indonesian banks. company value, both partially and simultaneously. The low adjusted R-squared indicates the dominance of external factors outside the model, while the mediation test confirms that ROA does not act as an intermediary. This reflect that integration aspect sustainability in assessment investors Still limited, so that required harmonization ESG reporting standards and fiscal incentives so that green practices can contribute significantly to market valuation premiums